AN OVERVIEW OF USING SOME ESSENTIAL OILS IN FUNCTIONAL DAIRY PRODUCTS FROM IRAN - Mahmoudi, Razzagh (Malaysian Journal of Science, 2014)
In the last few years more and more studies on the biological properties of essential oils (EOs) especially antimicrobial and antioxidant properties in vitro and food model have been published in all parts of the world. But so far no comprehensive reports of these studies have been reported in food model from Iran. The focus of this overview lies in the using of EOs from some indigenous medicinal plants of Iran (including: Mentha longifolia, Cuminum cyminum, Teucrium polium, Pimpinella anisum and Allium ascalonicum) in probiotic dairy products (especially cheese, yoghurt and Aryan) in recent years. Recently, consumers have developed an everincreasing interest in natural products as alternatives for artificial additives or pharmacologically relevant agents. Among them, EOs has gained great popularity in the food, cosmetic, as well as the pharmaceutical industries. Despite the reportedly strong antimicrobial activity of EOs against food-borne pathogens and spoilage microorganisms, their practical application as preservatives is currently limited owing to the undesirable flavor changes they cause in food products. Nonetheless, more studies are necessary to the applicability of various EOs on other food models in Iran and other countries. (Keywords: EOs, Functional Diary Foods, Natural preservative, Sensory quality)